Analisis Gangguan Pada Sistem Tenaga Listrik Jawa Bali 500 kV Menggunakan Power World Simulator - Dwi Ajiatmo; Imam Robandi; Machrus Ali (FT- UNDAR, 2019)
Short circuit is one type of interference that often occurs in electric power systems. The interference if it lasts a long time will affect the quality and continity of electrical power distribution as well as the reliability and safety of the equipment on the system. To minimize the possibility of interference and to minimize the consequences caused by interference, an analysis of disturbances in the electric power system is needed. This study discusses the classification and analysis of disturbances in the electric power system. The type of interference in the electric power system is classified into two, namely symmetry and non-symmetrical interference. Symmetry disturbances are three phase disturbances which are described by the equation of the sequence of the symmetry component system. Sequence equations from the symmetry component system are positive sequence equations, negative sequence equations, and zero sequence equations. Non-symmetrical interference is a disorder that often occurs in electric power systems, namely the interference of one network to the ground, network interference to the network and interference of two networks to the ground. This research is to classify and to analyze the types of disturbances in the Java-Bali electric power system 500 kV 20 buses in the form of a single line diagram, using Power World Simulator and ETAP Software applications. The simulation results are calculated and display the simulation design of the power system with the tools contained in the program.